Immodest and proud - Tallant, Jonathan (Springer, 2015)
In his ‘Ambitious, Yet Modest, Metaphysics’, Hofweber (Metametaphysics, Oxford University Press, Oxford, pp 260–289, 2009a) puts forward arguments against positions in metaphysics that he describes as ‘immodest’; a position he identifies as defended by Jonathan Lowe. In this paper I reply to Hofweber’s arguments, offering a defence of immodest metaphysics of the type practiced by Lowe (The possibility of metaphysics, Oxford University Press, Oxford, 1998) inter alia.